FORMY DEMOKRACJI WEWNĄTRZSPÓŁDZIELCZEJ W SPÓŁDZIELNIACH MIESZKANIOWYCH I ZASADA RÓWNYCH PRAW CZŁONKOWSKICH - Niedbała, Zdzisław (Wydział Prawa i Administracji UAM, 2009)
A co-operative, which is a voluntary and self-governing corporation, is organised and functions on democratic principles. One of the fundamental features of that democratic system is the fact that the role of the highest organ of a co-operative is vested in the general assembly of its members. The general assembly functions either directly, with participation of its all members, or indirectly, through their democratically elected representatives. The indirect form of representation is justified and usually preferred when a convention of a general assembly of all members is technically or organisationally difficult or impossible. Members of a co-operative have equal rights and obligations arising from membership, which is also manifested in the ‘one member - one vote’ principle. The objective of the paper is a critical account of selected legal solutions introduced in 2007 to the regulations concerning housing cooperatives from the point of view of internal democracy and equal membership rights.
FORMS OF INTERNAL DEMOCRACY IN HOUSING CO-OPERATIVES AND THE PRINCIPLE OF EQUAL MEMBERSHIP RIGHTS